Peran KUA dalam Mencegah Pernikahan Dini di Bawah Umur - Reza Artanasia; Abdul Rahman Sakka; Abdul Salam (Al-Azhar Islamic Law Review, 2023)
This study was conducted with the aim of knowing, the causes of underage marriage during the covid-19 pandemic in the Ujung Bulu sub-district, Bulukumba Regency, the role of the religious affairs office in preventing underage marriage during the Covid-19 pandemic in the Ujung Bulukumba sub-district. This research is a field research using descriptive qualitative method. The approach used in this research is a normative and empirical juridical approach with data collection techniques through observation, interviews and documentation. There are two data obtained in this study, namely primary data and secondary data. Primary data were obtained through interviews with the head of the religious affairs office in the Ujung Bulu sub-district, the head of the KUA in the Ujung Bulu sub-district, the KUA extension in the Ujung Bulu sub-district, the service administration staff, the KUA operator staff in the Ujung Bulu sub-district, as well as some people who have underage marriages. while secondary data is data arranged in the form of documents. The results of this study indicate that (1) the cause of underage marriage during the covid-19 pandemic in the Ujung Bulu sub-district is caused by several factors, namely, promiscuity, economic limitations, the influence of customs (habits. (2) the role of KUA in preventing cases of marriage under During the covid-19 pandemic in Ujung Bulu sub-district, there was an MOU (Cooperation) with schools by socializing with school children in Ujung Bulu sub-district regarding their right to learn at their age, as well as outreach to the community through the pulpit, ta'lim assembly, and implement work programs from the Bulukumba Regency Ministry of Religion (KEMENAG) office in the form of school age guidance and work together with local governments such as (police, sub-district, village heads and health centers in terms of minimizing (preventing) the occurrence of underage marriages that occur in the Ujung Bulu sub-district, Kabupaten Bulukumba.